2015
DOI: 10.1177/1060028015593763
|View full text |Cite
|
Sign up to set email alerts
|

Medication Discontinuation in Patients After Discharge From a Psychiatric Hospital

Abstract: Discharge from a psychiatric hospital led to medication discontinuation in approximately 70% of all patients. Approximately 40% of the patients discontinued medications for chronic conditions. Discontinuation of somatic medication was more frequent than discontinuation of psychiatric medication, and risk of discontinuation was lower for patients with depressive and anxiety disorders. Although medication discontinuation can be deliberate it is alarming that a quarter of our patients using antipsychotics and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The majority of studies investigating medication changes after discharge have focussed on general or psychiatric hospital settings [ 4 ]. Little is known about medication changes in patients with PD after discharge from a movement disorder unit.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies investigating medication changes after discharge have focussed on general or psychiatric hospital settings [ 4 ]. Little is known about medication changes in patients with PD after discharge from a movement disorder unit.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed a nonadherence rate of 43% to prescribed medications among non-forensic psychiatric outpatients (4). Post-discharge, 68% of general psychiatric patients discontinued their psychiatric medication, and 25% discontinued using antipsychotics within 3 months after discharge (5). Research focusing only on individuals with schizophrenia indicated that as many as 74% of the group discontinued the specific type of pharmacological treatment within 18 months (6).…”
Section: Introductionmentioning
confidence: 99%